An Evaluation of Quality of Life after Ventral Hernia Repair Using the EuraHS-QoL Score: a Cross-Sectional Survey - Harshit Kumar Prabhakar; Vipin V Nair; Pranay Pratap; Sarath Kumar; Brig Alok Bhalla (Lietuvos Chirurgija)
Introduction. Recurrence rates for ventral hernia repairs are practically negligible because of advancements in surgical procedures. Pain and suffering, which significantly lowers patients’ quality of life, are currently the main concerns with ventral hernia repair rather than the possibility of recurrence. This study used “EuraHS-QoL” score for evaluating the quality of life of patients before and after ventral hernia repair. Methods. A prospective observational study involving patients with ventral hernias receiving surgery from May to December 2023. Using the EuraHS-QoL questionnaire, patients’ quality of life was evaluated both before and after surgery. Results. Of the 53 patients, 17 (32%) were men and 36 (68%) women, with a mean age of 49.71±10.9 years (range, 32–68 years). BMIs averaged 25.4±3.4 kg/m2, range (21.25 to 35.4 kg/m2). The majority of pain was from regular duties. By frequency, umbilical (22%), infraumbilical (43.3%), supraumbilical (5.7%), and numerous (19%) hernia sites exist. Three patients suffered surgery site infections and one had skin dehiscence. All patients showed overall improvement of QoL at the end of 90 days.